Tumor stroma manipulation by MSC - Grisendi, Giulia; Fiori, Agnese (Current drug targets, 2016)
Tumor stroma (TS) plays relevant roles in all steps of cancer development. We here address several fundamental aspects related with the interaction between cancer cells and their stromal counterparts. Dissecting these players is of pivotal importance to understand oncogenesis, immunoescape and drug resistance. In addition, this better comprehension will allow the introduction of novel and more effective therapeutic approaches where manipulated stromal elements may become detrimental for tumor growth. Our group and others rely on the use of multipotent mesenchymal stromal/stem cells (MSC) as anti-cancer tools, since these putative TS cell precursors can deliver potent apoptosis-inducing agents. Multimodal-armed MSC can target a variety of cancers in vitro and, when injected in vivo, they localize into tumors mediating cell death without evident toxicities to normal tissues. While several aspects of these strategies shall require further investigations, these approaches collectively indicate how TS manipulation by MSC represents a tool to influence the fate of cancer cells, creating a new generation of anti-cancer strategies.